CURRENT PHARMACOLOGICAL STATUS OF CARDIOPROTECTIVE PLANTS AGAINST ISOPROTERENOL INDUCED MYOCARDIAL INFARCTION - Fathima, Syeda Nishat; Murthy S, Vasudeva (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Cardiovascular diseases are the major cause of morbidity and mortality in the modern era. Myocardial infarction is a condition where there is a significant decrease or block in the blood (oxygen) supply to the part of heart, leading to degeneration of a portion of the myocardium which triggers a cascade of cellular, inflammatory and biochemical events, leading eventually to the irreversible death (necrosis) of heart muscle cells. Various therapeutic interventions, including lifestyle modification, pharmacological treatment options, and surgical techniques are available. The present review focus on the plants that have been evaluated for cardioprotective activity against isoproterenol-induced myocardial infarction. Method: The current status of Cardioprotective plants was obtained from a literature search of electronic databases such as Google Scholar, Pubmed and Scopus up to 2017 for publications on medicinal plants used against isoproterenol-induced myocardial infarction. Isoproterenol, Isoprenaline, myocardial infarction, cardioprotective were used as keywords for the searching. Result: A total of 117 different plant parts and their extracts have till now been published to possess cardioprotection against isoproterenol-induced myocardial infarction. Isoproterenol a beta-adrenergic receptors agonist causes severe stress in myocardium resulting in the infarct-like lesion and produced cardiotoxic effects by elevating the levels of cardiac biomarkers and causing changes in ECG. Plant-based medicines with their antioxidant, antiapoptotic, antihyperlipidemic, platelet antiaggregatory, anti-lipid peroxidation property provide substantial evidence for the management of Ischemia. Conclusion: This review, therefore, provides a useful resource to enable a thorough assessment of the profile of plants that have cardioprotective activity against isoproterenol-induced myocardial infarction.